Preparation and performance evaluation of cyclodextrin bifunctional monomer molecularly imprinted polymers - YU Haining; HUANG Haiyong; HE Chengzijing; LAY Sovichea; SHEN Shengrong (浙江大学学报. 农业与生命科学版)
The preparation and performance evaluation of the cyclodextrin bifunctional monomer molecularly imprinted polymer were studied. A series of di (2-ethylhexyl) phthalate (DEHP) imprinted polymers were prepared using allyl-β-cyclodextrin (allyl-β-CD) either alone or in conjunction with methacrylic acid (MAA), methyl methacrylate (MMA), acrylonitrile (AN), and acrylamide (AA) as the binary functional monomers. According to values of the binding specificity experiment, the binary functional monomers (M-MAA, M-MMA, and M-AN) were superior to a single functional monomer (M-β-CD); the average value of bound substrates from binary functional monomers was 110 μmol/g, whereas a single was 90 μmol/g. When M-MAA, M-MMA and M-AN were chosen as the stationary phase for molecularly imprinted solid-phase extraction (MISPE) and used to analyze the spiked infant formula, the recovery rate of DEHP ranged from 89.06% to 97.98% with relative standard deviations (RSD)≤6.47%. In addition, computational simulation results showed that MAA and AN had the strongest binding capacity with template molecules. All in all, the productions of binary functional monomer-synthesized molecularly imprinted polymer (MIPs) have yielded higher binding ability than that of single ones and are efficient separation of hydrophobic molecules.